Pengaruh Penggunaan E-Learning Quipper School terhadap Hasil Belajar Kognitif Siswa Kelas XI SMA ITCI PPU pada Materi Termokimia - Sri Lestari; Yuli Hartati; Yeyen Adzikah Indriantoro (Polygon : Jurnal Ilmu Komputer dan Ilmu Pengetahuan Alam, 2025)
Quipper School E-Learning is a learning media with an E-Learning system based on open source which is a link between students and teachers in the division of tasks online. Learning using the E-Learning Quipper School media can be done anywhere, providing teaching materials according to the curriculum, students can see the value of learning otcomes directly, students and teachers can discuss through this media so that students become more active. The purpose of this study was to determine the effect of using Quipper School e-learning media on the learning outcomes of class X High School of ITCI Penajam Paser Utara on the nomenclature of chemical compounds. The type of research used is quasi-experimental research with a Post Test Only Control Group Design. The population in this study were all class X students of High School of ITCI Penajam Paser Utara for the 2023/2024 academic year. Class XI-2 as an experimental class that uses Quipper School e-learning media and Class XI-1 as a control class that does not use Quipper School e-learning media. Data collection uses tests in the form of post-tests and daily tests as well as non-tests, namely student response questionnaires, observation sheets of teacher and student activities. The results of data analysis show that the value of learning outcomes in the experimental class is 86, higher than the control class which is 81, so it can be concluded that the use of Quipper School e-learning has an effect on students' cognitive learning outcomes in thermochemical material.